An analysis of directive speech act found in “M3GAN” movie (2023) - Putri, I Gusti Ayu Intan Triana; Tustiawati, Ida Ayu Mela (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The objective of this research is to examine the various forms of directive expressions in the 2023 film “Horror Megan,” The researchers employed Yule’s theory of speech acts for this investigation. A qualitative approach was utilized by the researchers to scrutinize the directive expressions present in the movie. During the analysis process, distinct categories of directive speech acts were identified. A total of 39 instances of directive speech acts were collected in this study. These instances were further classified into four subcategories: asking (17 instances), ordering (14 instances), requesting (5 instances), and suggesting (3 instance). Furthermore, the researchers provided insights into the underlying purposes of each type of directive speech act throughout the narrative. In this study only found four types of directive illocutionary act, they are asking, ordering, requesting and suggesting. Among all the data collected from the movie, the predominant form observed in this study was Asking, which was the most prevalent.